Strengthening cybersecurity education for university students: bridging vulnerabilities and promoting proactive digital safety practices - Anxhela Ferhataj; Fatmir Memaj; Roland Sahatcija; Ariel Ora (Millenium)
Introduction: As university students in emerging regions like Albania increasingly engage with digital platforms, they face growing cybersecurity risks. While basic tools like antivirus software are common, critical gaps in password management and phishing detection persist, underscoring the urgent need for enhanced cybersecurity education.